Antibiotic resistance and resistance genes in Escherichia coli from poultry farms, southwest Nigeria - Olawale O Adelowo; Obasola E Fagade; Yvonne Agersø (Journal of Infection in Developing Countries)
Introduction: This study investigated the mechanisms of resistance in 36 E. coli isolated from waste, litter, soil and water samples collected from poultry farms in Southwestern Nigeria. Methodology: Minimum inhibitory concentration (MIC) distributions of the isolates were determined using the methods of the Clinical and Laboratory Standard Institute and resistance genes detected by PCR. Results: A total of 30 isolates (94%) showed resistance to more than one antimicrobial. Percentage resistance was: tetracycline 81%, sulphamethoxazole 67%, streptomycin 56%, trimethoprim 47 %, ciprofloxacin 42%, ampicillin 36%, spectinomycin 28%, nalidixic acid 25%, chloramphenicol 22%, neomycin 14%, gentamicin 8%, amoxicillin-clavulanate, ceftiofur, cefotaxime, colistin, florfenicol and apramycin 0%. Resistance genes found among the isolates include bla-TEM (85%), sul2 (67%), sul3 (17%), aadA (65%), strA (70%), strB (61%), catA1 (25%), cmlA1 (13%), tetA (21%) and tetB (17%). Class 1 and 2 integrons were found in five (14%) and six (17%) isolates, respectively, while one isolate was positive for both classes of integrons. Seven out of eight isolates with resistance to ciprofloxacin and MIC ≤ 32 mg/L to nalidixic acid contained qnrS genes. Conclusions: Our findings provided additional evidence that the poultry production environment in Nigeria represents an important reservoir of antibiotic resistance genes such as qnrS that may spread from livestock production farms to human populations via manure and water.